LEGAL PROTECTION AGAINST E-SPORT PLAYER LOSSES COMMITTED BY ONE OF THE MANAGEMENTS IN INDONESIA - Sari, Yunita Puspita; Perdana, Siska Wahyu; Nur Kholis, Saddam Harits; Wildana, Nabila (Universitas Negeri Surabaya, 2024)
Violence in football in Indonesia has become a recurring and concerning problem. Violent incidents between supporters, players and security forces often occur, tarnishing the image of sport which should prioritize sportsmanship and unity. This incident was not only physically detrimental, but also had a negative impact on the development of national football. The role of law in dealing with violence in the game of football is very important in regulating the behavior of players, officials and fans as well as in enforcing rules to maintain safety and security. This study examines the role of law from two main perspectives: regulatory and enforcement. From a regulatory perspective, the law plays an important role in determining the rules and regulations governing behavior on the field, including stadium policies, spectator rules and sanctions for violators. On the other hand, in enforcement, the law acts as a tool to enforce these rules and apply consequences to violators, whether through disciplinary action from the football federation or criminal legal processes. The normative legal research method was chosen as the method in this research. The aim of this research is how the law can be an effective tool in overcoming violence on the football field, creating a football environment that is safe, fair and has integrity.